Effectiveness of AI App “Evolve” in Stress Management amongst Medical Students at Fazaia Medical College, Islamabad – A Quasi-Experimental Study - Muteebah Mansoor, Arham Zaheer, Maroosha Tahir, Ishrat Huma Zaffar, Valeeja Murad, Zille Huma Mustehsan, Iffat Noreen, Farah Rashid (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Mental health is one of the most common concerns amongst medical students. One in three medical college students struggle with mental health. This study highlights the critical need to address mental health issues and promote students’ holistic well-being. Digital mental health interventions offer the possibility of treatment to college students with common mental health problems. Aim: To determine the effectiveness of an AI mental health app, “Evolve,” in assisting with stress management. Results: A quasi-experimental (Pre and Posttest) study was conducted at Fazaia Medical College. Participants were assessed for stress using the PSS scale. They were separated into a control and an interventional group, with the interventional group using the “Evolve” App. Post-intervention analysis indicated a significant reduction in stress levels among regular app users, revealing a positive correlation between app usage frequency and reduced stress. Conclusion: The research accentuated the efficacy of the AI app Evolve in alleviating stress amongst medical students. It not only validated previous theories about the potential of smartphone-based AI apps in stress management but also provided a significant scheme for future mental health management in colleges. Keywords: Digital interventions, AI, Mental Health, Stress management, medical student